THE STUDENTS’ PERCEPTION TOWARDS READING STRATEGIES AT 2ND SEMESTER STUDENTS OF STBA JIA IN ACADEMIC YEAR 2021/2022 - Esterria Romauli Panjaitan; Fitra Mandela; Ade Surista (IKIP Siliwangi, 2024)
This study discussed STBA JIA students’ perception of reading learning in the 2nd semester of academic year 2021/2022 of STBA JIA, Bekasi”. The purpose of this study is to investigate students' perceptions of reading strategies and to demonstrate that reading strategies can help students continue their learning to the next level. This research is carried out utilizing a qualitative research method, namely a descriptive design. The total number of students was 51 students of 2nd semester, and the data was collected through interviews questionnaires. The data analysis technique used was to explain the data from the questionnaire, which was handled using Google Forms. Google Form serves as a digital form to gather data in this study, and the findings serve to analyze the data. To put it another way, it was transformed into a pie or bar chart. The findings revealed that, in general, students' perceptions of reading strategies were favorable (positive), since most of them still pay attention and perform pre-reading, during reading, and after reading strategies. Reading strategies will always help and support the students in their reading comprehension performance.